Agrotechnological characteristics of sugarcane cultivars irrigated with salinized water - Eduardo M. O. Laime; Pedro D. Fernandes; Lenildo T. Souto Filho; Mirandy dos S. Dias; Francisco de A. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT With the expansion of sugarcane cultivation in the semiarid region of Brazil, there is a constant risk of soil salinization because of the edaphoclimatic peculiarities of the region, requiring studies to identify genotypes tolerant to salt stress. This study evaluated the agrotechnological characteristics of sugarcane cultivars irrigated with salinized water. This study was performed in the experimental area of the Academic Unit of Agricultural Engineering of the Federal University of Campina Grande, Paraíba, Brazil. The treatments consisted of a combination of two sugarcane cultivars (SP 81 3250 and RB 92 579) and five levels of electrical conductivity of irrigation water (0.6, 1.6, 2.6, 3.6, and 4.6 dS m-1). A randomized block design was used in a 2 × 5 factorial scheme with four replicates, totaling 40 experimental units. The sugarcane cultivar SP 81 3250 under irrigation with saline water of 0.6, 1.6, and 2.6 dS m-1 promoted a greater number of leaves in relation to RB 92 579, 125 days after planting. The salinity of the irrigation water varying from 0.6 to 4.6 dS m-1 reduces the culm height and culm mass per clump of the sugarcane, regardless of the cultivar. The sugarcane cultivar RB 92 579 had the highest culm height, number of tillers, culm mass per clump, percentage of apparent sugars, soluble solids, polarized sucrose, and total recoverable sugars, whereas SP 81 3250 had the highest percentage of water-insoluble matter contained in the cane, regardless of water salinity.